NON-INVASIVE DIAGNOSTICS OF LIVER FIBROSIS IN PATIENTS WITH CHRONIC HEPATITIS B AND C - Bokieva Charos Sharofovna; Tilloyeva Shakhlo Shavkatovna (KONFERENSIYALAR, 2025)
Resume.  Chronic  diffuse  liver  diseases,  especially  viral  liver  damage,  are one of the most urgent problems of modern hepatology. The aim of the study was to conduct a clinical assessment using ultrasound Dopplerography and ultrasound elastometry  for  non-invasive  diagnosis  of  liver  fibrosis  in  patients  with  chronic hepatitis.  In  a  comparative  analysis  using  non-invasive  diagnostic  methods  to assess the degree of liver fibrosis, ultrasound elastometry is more informative than ultrasound Doppler.